Polymer-supported bis-cinchona alkaloid ligands for asymmetric dihydroxylation of alkenes - a cautionary tale - Canali, L; Song, CE; Sherrington, DC (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
Careful work-up and purification of purported copolymers formed by free radical copolymerisation of a bis-cinchona alkaloid with methyl methacrylate shows that the level of incorporation of the bis-alkaloid into the polymer skeleton is below the detection limit of a routine nitrogen microanalytical protocol. This reluctance of the C=C bonds in the bis-alkaloid to undergo copolymerisation with a methacrylate monomer is totally consistent with the well-known and extensively documented poor copolymerizability of allylic monomers. Direct free radical copolymerisation of allyl groups containing alkaloids and other allyl substituted optically active ligands is not therefore a general and simple option for the production of polymer-supported asymmetric catalysts. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: CATALYSTS; OLEFINS